POTENTIAL REVENUE OF VALUE ADDED TAX FROM TRADE TRANSACTIONS THROUGH THE ELECTRONIC SYSTEM - Agrevinna Beatrice; Sri Yani Kusumastuti (Jurnal Apresiasi Ekonomi, 2023)
This study aims to estimate the potential revenue of taxing the digital commerce transaction in Indonesia by implementing Value Added Tax on e-Commerce. The estimation is calculated from Indonesia’s electronic commerce projection from Statista in three scenarios, optimistic scenario, moderate scenario, and pessimistic scenario. The estimated VAT on e-Commerce revenues from these three scenarios are then compared with the VAT revenue in State Budget 2020. The estimations show that imposing VAT on e-commerce can raise 3,02-5,35% VAT revenue target in 2020.